Adaptation and tolerance in extreme situations - Вакуленко, Валентина Миколіївна (Pedagogy of Higher and Secondary Education, 2017)
The author examines the role of adaptation and tolerance in extreme situations, in self-awareness, self-realization of human creativity. That is very important for the process of socialization of personality. The essence of the concepts of «stress» and «social pedagogical adaptation» are analyzed; factors that contribute to the development of stress are referred; strategies of tolerant behavior are discussed. Human behavior can be seen as a function of the interaction of personal potential and situation at any given time. Strategies of tolerant behavior – a special motivational syndrome, are characterized by updating the adaptive mechanisms of self-regulation, self-control in extreme conditions. Strategy of tolerant and adaptive behavior is a strategy of self-reliance, courage, the will of man, actualization, mobilizing his/her capacity to overcome extreme situations. Individual human characteristics are seen as opportunities realized in acts of behavior in a particular difficult situation. And each person should be prepared not only passivelybut also actively to express their attitude to overcome arisen severe and sometimes extreme situations. The need for self-defence – is the most important existential human need that must be implemented on time, and one should not expect that everything will be resolved by itself. During the life path of a man inevitably more and more difficult situations that include extreme appear and disappear. This process is accompanied by continuous changes of a person and situations and circumstances. However, the most important are the changes that lead to significant transformations of a situation that is a new event and a new kind of «birth» of a person. An extreme situation – is at the same time, not a cure, and in most cases the most vital issue. But if it happened – there is a need to mobilize human potential, if it is a will, self-sufficiency, self-esteem and desire to overcome themselves «I can do it!».